Eulophidae novae germanicae (Hymenoptera: Chalcidoidea). - Erdös, József (Contributions to Entomology = Beiträge zur Entomologie, 1956)
Nomenclatural ActsHalochariessa Erdös, 1956 (Eulophidae), gen. n.germanica Erdös, 1956 (Halochariessa), spec. n.pannonica Erdös, 1956 (Halochariessa), spec. n.